If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(x + 3) = 36 Reorder the terms: x + -2(3 + x) = 36 x + (3 * -2 + x * -2) = 36 x + (-6 + -2x) = 36 Reorder the terms: -6 + x + -2x = 36 Combine like terms: x + -2x = -1x -6 + -1x = 36 Solving -6 + -1x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 36 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 36 + 6 -1x = 36 + 6 Combine like terms: 36 + 6 = 42 -1x = 42 Divide each side by '-1'. x = -42 Simplifying x = -42
| -8z(w-6)=32 | | 4xn-7=41 | | X/3+10=16 | | 1/2(4x-6y) | | 2x-6+3x=29 | | 1280/90*2 | | 0.1z=2 | | 9x^6=0 | | -15-3x=X+13 | | 9x^9=0 | | 6x^5(-6x^5-3)= | | -78=6(-2+3a) | | -40/y^2-12y+27=2y/y-3 | | 8x+x^2=48 | | 0=4x^2+x-5 | | 7x+258=2x+66 | | 7y-7x=1 | | 33-(-15)+(-8)-2= | | 5x+12=40 | | 9*2/3 | | f(x)=4x^3-18x^2+24x-8 | | 8+3-4= | | 10(2x-5)=30 | | .8k=-12 | | f(x)=x^3-x^2-2x+3 | | 6t-5=4t-1 | | 0=30-34x+3x^2 | | 12x-3x+2x=7766 | | Y=6x^2+11x+3 | | 2.50x+3.50(8-x)=23.00 | | 5x+12=50 | | 0=30-3x+3x^2 |